Retrospective Analyses of Orofacial Traumatic Injuries in Trauma Patients, Registered as Medicolegal Cases at a Tertiary Care Hospital in Delhi - Khatri, Amit; Kalra, Namita; Bakshi, Radhika (Journal of Orofacial Research, 2014)
Aim: The purpose of this retrospective study was to determine the etiology, occurrence and the pattern of orofacial traumatic injuries in trauma patients, registered as medicolegal cases, managed by the Dental Unit of the Accident and Emergency Department at the UCMS and GTB Hospital, Delhi. Materials and methods: Dental case record of 1289 medicolegal patients (from January 2011 to December 2011) reported to UCMS and GTB Hospital Emergency, Delhi were analyzed. The age, gender, month, etiology and type of injury were the different variables that were recorded. Results: Orofacial trauma was more common in males (1052, 81.52%) compared to females (237, 18.75%). Male to female ratio was (4.438:1). The main etiologic factor involved in orofacial trauma was physical assault (54.29%) and road traffic accident (34.52%). Age distribution peak was observed in 21 to 25 age group (19.68%).The prevalence of trauma through out year showed proportionality, being observed a larger of cases between month April and June. Conclusion: Based on the obtained data it may be concluded that appropriate policies of orofacial trauma prevention must be established. Strict legislation against violence and stricter implementation of traffic rules must be followed.